Mastering SQL server 2005 reporting services infrastructure design - Jorden, Joseph L. (Wiley Pub, 2007)
Reporting Services is a powerful tool for SQL Server 2005 database administrators, developers, and other IT professionals, enabling them to make sense of the immense amount of data generated by enterprises of all sizes Shows readers how to create, manage, and distribute information as well as how to design, produce, and distribute reports that meet the needs of the stakeholder. Contains practical insights and real-world solutions not found in other books. Bridges the gap between those who manage data and those who need it